1980
DOI: 10.1136/oem.37.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in workers exposed to polyvinyl chloride dust.

Abstract: Several reported studies on the effects of polyvinyl chloride (PVC) dust in animals and man have been conflicting. The present study of the ventilatory function of 509 male workers exposed to PVC dust was made in 1977. Altogether 104 men exposed to PVC dust only, 112 men exposed to non-chlorinated solvents only, and 293 men exposed to a mixture of both completed the MRC questionnaire on respiratory function and performed simple spirometric tests (forced expiratory volume in one second and forced vital capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
3

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 6 publications
1
9
0
3
Order By: Relevance
“…Konu hakkında yapılan araştırmalar, PVC toz maruziyetinin hem obstrüktif hem de restriktif solunum fonksiyon bozukluğuna yol açtığını göstermektedir (14). Ça-lışmalarda 6-12 yıllık uzamış maruziyetin veya 20 yıl-dan daha uzun süreli maruziyetin tütün alışkanlığından bağımsız olarak FEV 1 /FVC oranını azalttığı ve %70'in altına düşürdüğü gösterilmiştir (15,16). Benzer biçimde PVC tozuna 10 yıldan daha fazla süre maruz kalmış ça-lışanların %50'sinden fazla bir kısmında FEV 1 /FVC oranının %75'ten düşük olduğu saptanmıştır (14).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Konu hakkında yapılan araştırmalar, PVC toz maruziyetinin hem obstrüktif hem de restriktif solunum fonksiyon bozukluğuna yol açtığını göstermektedir (14). Ça-lışmalarda 6-12 yıllık uzamış maruziyetin veya 20 yıl-dan daha uzun süreli maruziyetin tütün alışkanlığından bağımsız olarak FEV 1 /FVC oranını azalttığı ve %70'in altına düşürdüğü gösterilmiştir (15,16). Benzer biçimde PVC tozuna 10 yıldan daha fazla süre maruz kalmış ça-lışanların %50'sinden fazla bir kısmında FEV 1 /FVC oranının %75'ten düşük olduğu saptanmıştır (14).…”
Section: Discussionunclassified
“…Ayrıca, PVC tozuna bağlı deskuamatif interstisyel pnömoni saptanmış bir olguda orta-akım hızlarında azalma bildirilmiştir (6). Ancak konu hakkındaki çalışmaların tümü bu sonuçları doğrulamamakta ve bazı çalışmalar PVC tozunun ventilatuvar fonksiyonlar üzerine çok ciddi bir etkiye neden olmadığını, hatta tümüyle etkisiz olduğu-na işaret etmektedir (12,13,16 Çalışmamızda günlük PEF değişkenliğinin tatil ve çalış-ma günlerinde hem idari hem de maruziyet grubunda anlamlı farklılık taşımadığını saptadık. Ancak toz maruziyeti olan grubun çalışma günlerindeki günlük PEF değişkenliğinin tatil günlerine kıyasla anlamlı oranda daha yüksek olduğunu tespit ettik.…”
Section: Discussionunclassified
“…It would appear, however, that, in many of the earlier studies, control of possible biases or confounding was less than adequate because of the lack of appropriate reference groups, failure to take into account the influences of age or cigarette smoking properly, or the absence of standardized procedures in radiographic reading such as the use of standard radiographs of the International Labour Office (lLO) or multiple readers blind to the exposure status of the subjects. Several studies have also provided conflicting evidence for lung function impairment (4,6,7).…”
mentioning
confidence: 99%
“…Since then, several epidemiologic studies have investigated the pulmonary effects of occupational exposure to vinyl chloride monomer (VCM) and polyvinyl chloride (PVC). These studies have shown an increased prevalence of radiological, lung function , or subjective abnormalities (2)(3)(4)(5)(6)(7)(8)(9). It would appear, however, that, in many of the earlier studies, control of possible biases or confounding was less than adequate because of the lack of appropriate reference groups, failure to take into account the influences of age or cigarette smoking properly, or the absence of standardized procedures in radiographic reading such as the use of standard radiographs of the International Labour Office (lLO) or multiple readers blind to the exposure status of the subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation